A Model for the Development of the Teacher Professional Learning Community Process of the Teacher Professional Internship Students, Faculty of Education, Nakhon Sawan Rajabhat University, By Promotional Activities on Professional Learning Community for Professional Ethics Development Via Information Technology System - Dee-Aim, Kraiwit (Arts of Management Journal, 2024)
This research aimed to (1) study the process of the professional learning community for teachers of teaching professional training students and (2) study guidelines for developing the process of learning communities. and 3) study teachers' opinions towards the teaching professional learning community process of teachers' professional training students, Faculty of Education. Nakhon Sawan Rajabhat University activities to promote the professional learning community process to develop professional ethics through information technology systems. The research findings revealed the following: 1) Components of developing the learning community process with activities to promote the professional learning community process to develop professional ethics through information technology systems, there are 11 elements, including 1.1) supporting education, 1.2) creating leadership, 1.3) exchanging experiences, 1.4) creating values, 1.5) Being a joint leader 1.6) Creating a conducive environment; 1.7) Creating a shared vision 1.8) Learning together; 1.9) Exchanging according to the era 1.10) Setting learning standards and 1.11) Application 2) Model for developing the process of a community of professional learning for teachers practicing professional experience in the Faculty of Education. Nakhon Sawan Rajabhat University activities to promote the professional learning community process to develop professional ethics through the information technology system, consisting of an introduction section, content section, and application section. 3) Evaluation of the model for developing the process of a teaching professional learning community for teachers' professional training students in the Faculty of Education. Nakhon Sawan Rajabhat University activities to promote the professional learning community process to develop professional ethics through information technology systems. Overall, it is at a high level.